Effects of pollen sources on the quality of nuts borne by pecan cultivars Kiowa and Barton - De Marco, Rudinei; Herter, Flávio Gilberto; Zoppolo Goldschmidt, Roberto José; Martins, Carlos Roberto; Crosa, Claudia (Comunicata Scientiae, 2023)
Selection of pecan cultivars and their pollinizers is essential to reach maximum potential of production. Synchrony of blooming periods of cultivars may not be enough to ensure nut quality because of the xenia effect. This study aimed at evaluating effects of different pollinizers on dimensions and yields of fruit borne by cultivars Kiowa and Barton. Both cultivars were submitted to six treatments. Kiowa: no pollination, free pollination, self-pollination and pollination controlled by pollen from cultivars Cape Fear, Pawnee and Desirable. Barton: no pollination, free pollination, self-pollination and pollination controlled by pollen from cultivars Melhorada, Jackson and Success. Self-pollination decreased dimensions and yields of fruit and kernels. Pollen from different cultivars was found to exhibit positive and negative xenia effect on fruit characteristics. The largest fruit and the highest yield of kernels were reached when ‘Kiowa’ was pollinized with ‘Desirable’ and ‘Barton’ was pollinized with ‘Success’.